2010
DOI: 10.1021/jp105700b
|View full text |Cite
|
Sign up to set email alerts
|

Adsorbate Effect on AlO4(OH)2Centers in the Metal−Organic Framework MIL-53 Investigated by Solid-State NMR Spectroscopy

Abstract: 1H and 27Al MAS NMR spectroscopies have been applied for studying the effect of water molecules, nitrogen bases, and o-xylene on the hydroxyl protons of bridging AlOH groups and framework aluminum atoms in the metal−organic framework (MOF) MIL-53. For water molecules adsorbed on the low-temperature form MIL-53lt, two 1H MAS NMR signals were found indicating the formation of different O−H···O hydrogen bonds to neighboring oxygen atoms, such as to carboxylic oxygens. Upon adsorption of the nitrogen bases acetoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 22 publications
6
69
0
Order By: Relevance
“…Theoretically, MIL-53(Al) is built up by aluminum atoms that coordinate to terephthalates as organic linkers. [17,24] In the regular hydrothermal synthesis of MIL-53(Al), aluminum is present as the Al(H 2 O) 6 3 + ion in the aqueous solution. The conversion can be described as the replacement of a water molecule from the [Al(H 2 O) 6 ] 3 + ion, thus resulting in the formation of AlO 4 (OH) 2 centers.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretically, MIL-53(Al) is built up by aluminum atoms that coordinate to terephthalates as organic linkers. [17,24] In the regular hydrothermal synthesis of MIL-53(Al), aluminum is present as the Al(H 2 O) 6 3 + ion in the aqueous solution. The conversion can be described as the replacement of a water molecule from the [Al(H 2 O) 6 ] 3 + ion, thus resulting in the formation of AlO 4 (OH) 2 centers.…”
Section: Resultsmentioning
confidence: 99%
“…In a number of solid materials, bridging OH groups (T(OH)T) between framework metal atoms T exist, also called structural OH groups. In the microporous metal-organic framework MIL-53, e.g., Al(OH)Al groups are formed at Al-O-Al bridges between two adjacent framework aluminum atoms [53,54]. The octahedrally coordinated framework aluminum atoms of MIL-53 are coordinated to four oxygen atoms of organic linkers and two oxygen atoms of the above-mentioned bridging OH groups causing 1 H MAS NMR signals at d 1H ¼1.7-2.6 ppm in the hydrated and dehydrated state (see Table 1).…”
Section: H Mas Nmr Spectroscopic Characterization Of Hydroxyl Protomentioning
confidence: 99%
“…Depending on the structure type of zeolites and their cation exchange degree, the 1 H MAS NMR signals of Si(OH)Al groups can be observed at d 1H ¼3.6-4.0 and 4.8-5.2 ppm due to bridging OH groups located in large cages and small structural units, respectively (see Table 1). The larger [54], parent zeolite H,Na-Y (n Si /n Al ¼ 2.7) (b), dealuminated zeolite deH,Na-Y/ 81.5 prepared by steaming at 748 K at a water vapor pressure of 81.5 kPa and not hydrated after steaming and nitrogen purging (c) [74], and the heteropoly acid AlPW 12 O 40 dehydrated at 473 K (d) [69]. Experimental spectra (top) are compared with simulated spectra (bottom).…”
Section: H Mas Nmr Spectroscopic Characterization Of Hydroxyl Protomentioning
confidence: 99%
See 1 more Smart Citation
“…[30][31][32][33] Recently, 129 Xe NMR was employed to investigate the Xe molecule itself in its adsorption to MIL-53 (Al). 34 However, solid-state 13 C NMR studies of CO 2 in MIL-53 have not been reported until now, even though 13 CO 2 can act as a direct probe molecule to examine the pore environments.…”
mentioning
confidence: 99%